2019
DOI: 10.5604/01.3001.0013.0400
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life in patients after cochlear implantation surgery in 2014-2017

Abstract: Introduction: Profound hearing loss significantly affects the quality of life of deaf people as well as their families. Observation of the benefit from the use of cochlear implants in deaf patients allows to assess the success of treatment with this method and its impact on the quality of life of these patients. The aim of this study was to determine the quality of life in patient after the cochlear implantation in the material of Department of Phoniatrics and Audiology of the Medical University in Poznań. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
2
4
0
2
Order By: Relevance
“…There were smaller declines in HRQoL scoring for the attributes emotion, cognition, and health utility during the time of follow-up; those changes were not significant and are not necessarily related to hearing function, as the majority of SSQ domains and the global score showed overall increases. The health utility score in this current study reported 0.481 at baseline, and 0.653 and 0.650, at YR1 and YR2, respectively, which also shows similarity to the findings of a previous IROS study [ 23 ]. The previous study included individuals aged 18–80 years of age, had a smaller sample size ( n = 70), and presented a health utility score of 0.49 at baseline and 0.56 at follow-up [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…There were smaller declines in HRQoL scoring for the attributes emotion, cognition, and health utility during the time of follow-up; those changes were not significant and are not necessarily related to hearing function, as the majority of SSQ domains and the global score showed overall increases. The health utility score in this current study reported 0.481 at baseline, and 0.653 and 0.650, at YR1 and YR2, respectively, which also shows similarity to the findings of a previous IROS study [ 23 ]. The previous study included individuals aged 18–80 years of age, had a smaller sample size ( n = 70), and presented a health utility score of 0.49 at baseline and 0.56 at follow-up [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Louise et al detected that three HUI3 subdomains of hearing, emotion, and speech significantly improved because of CI [ 10 ]. Hanna et al reported that patient only hearing and speech scores improved significantly according to HUI3 measurement after CI [ 11 ]. Summerfield's study reported great change in hearing and speech using HUI3 and a difference in depression using EQ-5D-3L [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have examined the impact of a CI on the health status of SSD patients. Czerniejewska-Wolska et al reported a multiattribute score of 0.56 one year after CI implantation [ 15 ]. Unfortunately, they did not report on the hearing status on the contralateral side.…”
Section: Discussionmentioning
confidence: 99%
“…An instrument for assessing the health-related QoL is the Health Utility Index (HUI), which is widely used to assess the cost-effectiveness of a treatment. The HUI was recommended for the assessment of health-related QoL in patients with SSD [ 14 ], and was used to document improved QoL after cochlear implant (CI) implantation [ 15 ]. To the best of our knowledge, only one center assessed health utilities based on HUI in a small group of BCI patients, and no correlation with objective hearing measurements exists [ 16 ].…”
Section: Introductionmentioning
confidence: 99%